2018
DOI: 10.1017/s1463423618000014
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis guideline awareness among Iranian family physicians: results of a knowledge, attitudes, and practices survey

Abstract: Although most family physicians believed in the importance of preventive measures, however, limited number of them had good knowledge and practice regarding osteoporosis and less than a quarter were aware of national guideline. This is a clear need to disseminate the guideline more effectively, make greater use of efficient training methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
3
19
3
1
Order By: Relevance
“…For the participant's attitude towards osteoporosis prevention and management, the majority of participants believed that osteoporosis has major impact on the health of individuals as well as the community in comparison with osteoarthritis with the percentage being 72% and 54%, respectively. This was in agreement with the Iranian study which noticed that only 30% did not consider osteoporosis as an important health problem 17 . Bisphosphonates are dominant inhibitors of osteoclastmediated bone resorption; therefore, these are mainly used in treating Osteoporosis 18 .…”
Section: Discussionsupporting
confidence: 92%
“…For the participant's attitude towards osteoporosis prevention and management, the majority of participants believed that osteoporosis has major impact on the health of individuals as well as the community in comparison with osteoarthritis with the percentage being 72% and 54%, respectively. This was in agreement with the Iranian study which noticed that only 30% did not consider osteoporosis as an important health problem 17 . Bisphosphonates are dominant inhibitors of osteoclastmediated bone resorption; therefore, these are mainly used in treating Osteoporosis 18 .…”
Section: Discussionsupporting
confidence: 92%
“…This study examines the university student's knowledge, attitude, and practices of osteoporosis risk factors in Jazan. The results revealed that the majority of the study participants were informed about the osteoporosis risk factors (Mahdaviazad et al, 2018). Among the targeted population, 91% recognized the proper definition of osteoporosis.…”
Section: Discussionmentioning
confidence: 97%
“…This includes the lack of knowledge about osteoporosis and the lack of treatment guidelines among family doctors and orthopedic surgeons. 16 , 17 , 19 , 22 , 23 In addition, orthopedic surgeons hardly accept their responsibility for the treatment of osteoporosis, as they are not familiar with the treatment of osteoporosis. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The correct treatment of osteoporosis was described by 4 R3 (21%), 2 R2 (9.5%) and 1 R1 (5%), showing some degree of learning during the years of residency, but still an important knowledge deficit at the time, similar to that described in orthopedics and general practice. 17 , 19 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%